PROBLEM SOLVING IN PULMONARY TUBERCULOSIS AMONG YOUNG ADULTS USING A FAMILY MEDICINE APPROACH: A CASE STUDY - Dwi Rahma, Anggun (JURNAL KEDOKTERAN RAFLESIA, 2025)
Tuberculosis is one of the oldest infectious diseases and remains a health problem in Indonesia and globally. The Tangerang Regency Health Office in Banten has identified 5,000 residents in the area who are suffering from or have been exposed to tuberculosis. One program considered successful, particularly in empowering family health, is the Family Folder program for TB patients. This qualitative study employed a case study design. It was conducted by observing and examining in depth the family’s influence on a single TB case using the Family Folder. Based on the results, it can be concluded that family participation is crucial for supporting the recovery of TB patients. Family support affects patient adherence to OAT therapy and influences the patient’s life and environment. This study also found an improvement in the family’s coping score, from 1 to 5, before and after the intervention, which included holistic and comprehensive management of TB patients. Keywords: family approach, pulmonary tuberculosis, adult patient